Pengaruh Profitabilitas Terhadap Harga Saham Perusahaan Manufaktur Pada Periode 2011-2015 - Endang Mahpudin (Accounthink, 2016)
This research is aimed to analyze the influence of profitability on the price of manufacturing companies share in the period of 2011-2015. Manufacturing industry sector is the main component of national ekonomi and as significant role within national development.Manufacturing companies are parts of industrial sectors that continue to develop in the current business world, with a constantly high transaction value in the stock exchange market. Besides, manufacturing companies are enterprises which have the highest number of emitters, which give significant influence to stock trade happening in Indonesian Stock Exchange Market (ISX). The object of this research is the stock price of manufacturing companies which is influenced by profitability. Meanwhile the research subject is manufacturing enterprises listed on ISX.Method applied in this research is quantitative method with case study approach Annual Financial Report year 2011 through year 2015. This method is used to see the influence of profitability on the price of manufacturing company share through the use of simple linear regression analysis. Based on data analysis results on manufacturing enterprises listed on ISX from year 2011 through year 2015, which are represented by: (1) PT Astra Internasional Tbk.;(2) PT Holcim Indonesia Tbk.; dan (3) PT Gudang Garam Tbk.,it can be concluded that profitability has significant influence on stock price change. Based on determinant coefficient calculation, the level of profitability influence on stock price is discovered to be 20.8%. Macro factors, such as market, inflation level and interest rate, fiscal and monetary policy, economic and international businesssituation also has influence on stock price. Micro factors, such as company revenue, shared dividend, cash flow, industrial fundamental change, and investment behavior change (from stock to obligation) has influence on stock price as well.